Robust Dynamic Inverse Controller for Spacecraft Model - Keream, Settar S.; Abdalla, Ahmed N.; Ruzlaini, Ghoni; Mohd Razali, Daud; Mashhadany, Youssif Al (World Wide Journals, 2014)
Typically, the spacecraft model has high uncertainties and the dynamic inverse inner loop controller alone may not achieve acceptable performance. Therefore, a robust outer loop must be added to compensate this inner- loop deficit. In this paper, a robust controller based on dynamic inverse technique for proto type vehicle X-38 model was proposed. The controller contains two loops. The inner loop is dynamic inverse controller which cancels existing system dynamics and replaces them with designer specified response, and the outer loop is a Linear Quadratic Gaussian (LQG) which is used as a robust approach. Several forms of desired dynamic are presented and evaluated in terms of performance and robustness including a proportional dynamics, proportional integral dynamics, flying quality dynamics and ride quality dynamics. The simulation results shows that flying quality and ride quality have been used as a desired dynamics. The ride quality has been proved to be more robust, then the other desired dynamics, against wide range of system parameter variation.